ANALISIS KESIAPAN MENGHADAPI DUNIA KERJA SETELAH PRAKTIK INDUSTRI MAHASISWA PENDIDIKAN TEKNIK MESIN FKIP UNS - Addin Nur Kasanah; Muhammad Akhyar; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The aims of this study are (1) to describing the work readiness of Mechanical Engineering Education students of Sebelas Maret University in dealing with the industrial sector after carrying out industrial training in terms of each indicator; (2) to describing the highest and lowest indicators of work readiness of industrial sector after industrial training owned by Mechanical Engineering Education students of Sebelas Maret University. The population in this study were all of Mechanical Engineering Education students who had carried out industrial training. The selected samples were 99 students of Mechanical Engineering Education. Instrument validity and reliability tests were carried out on 30 UNS Mechanical Engineering Education students who had carried out industry training and were chosen randomly. The results of the instrument validity test resulted in 51 valid statement items and 16 invalid statement items of 67 instrument items. Instrument reliability test used IBM SPSS Statistics version 21, this test resulted that the reliability value of 0.935. The results of the study revealed that work readiness of Mechanical Engineering Education students of Sebelas Maret University  in terms of the overall indicators in the medium category. The highest category of work readiness indicator of Mechanical Engineering Education students is on emotional indicator with a value of 20,7%. The lowest category of work readiness indicator of Mechanical Engineering Education students is on skill indicator with a value of 20,7%.